Factors affecting Organizational Citizenship Behavior and Health Worker Innovative Behavior: The Role of Person-Job Fit as a Moderating Variable - Yanto Tjoa; M. Arief (Journal of International Conference Proceedings, 2021)
This research aims to determine factors affecting organizational citizenship behavior and health worker innovative behavior such as transformational leadership, perceived organizational support, innovative work behavior, employee creativity, with person-job fit as the moderating variable. This research is included in descriptive quantitative research with a quantitative approach. The data analysis technique in this study used Partial Least Square (PLS). PLS is a Structural Equation Modeling (SEM) equation model with an approach based on variance or component-based structural equation modeling. The results of this research show that of several factors related to employees and their organizations, only transformational leadership that does not affect innovative work behavior.